Medicinal plants in pregnancy and lactation: perception of the health risk and practical educational group in Araraquara, São Paulo State, Brazil - Moreira, Raquel Regina Duarte [UNESP]; Camargo, Francisco Ribeiro [UNESP]; Quílez, Ana Maria; Salgueiro, Lígia; Cavaleiro, Carlos (OMICS International, 2014)
The use of medicinal plants among pregnant women and lactating is a common practice in diverse countries. However, many medicinal plants are contraindicated during pregnancy and lactating, due to various adverse effects, such as teratogenic, embryotoxic and abortive effects, exposing these women, their fetus and babies to health unknown risks. Thus, the purpose of this commentary, was to analyze the perception about the use of medicinal plants by pregnant women and lactating registered in the "baby on board" NGO, Araraquara, São Paulo state, Brazil, between 2010 at 2013. The group was constituted by 48 women, between the first and last trimester of pregnancy or whilst breastfeeding. Information was collected during group meetings by oral interview, using a questionnaire, as script. The nature of the study was a qualitative analysis. The results were based on reports about the use of medicinal plants by pregnant women during group meetings: use, indication of use, knowledge about risks. All participants received written and oral information about the study and they gave a written informed consent. The use of medicinal plants is a reality among pregnant and lactating women of the "baby on board" NGO. They reported that they feel that "natural" products are not harmful for their health. The primary information sources for the majority of women about medicinal plants during pregnancy are family, neighbors and herbalists. The plants most cited (in popular name in Brazil) were: senna, chamomile, boldo, lemon balm, lemon grass. They were used mainly for: nausea, heartburn, indigestion, flatulence, intestinal and abdominal pain, anxiety, intestinal constipation and low milk production. The pregnant and lactating women lacked knowledge about the health risks of the use of medicinal plants and herbal medicines in pregnancy and lactation. They also reported difficulties in clarifying some questions about the use of medicinal plants with their doctors. The results of the present study showed that educative actions about the rational use of medicinal plants in pregnancy and breastfeeding could be part of the operating protocols to promote the maternal and child health programs in Araraquara. Thus, our results also suggest the importance of creating institutionalized places, to the implementation of continued education programs about rational use of medicinal plants in pregnancy and lactation. These targeted programs are not only for health professionals, but also for community members, pregnant women and breastfeeding. Our results pointed out the importance of guidance of doctors and healthcare professionals on the scientific studies about medicinal plants and herbal medicines and the risk/benefit of using herbs during pregnancy. Finally, it is noted the importance of the health professionals to inform women of childbearing on risks to their health, as well as on possibilities of utilization of herbs during fertile period, giving special attention to the potential risk of self-medication.
Keywords: Pregnancy; Breastfeeding; Educative group; Medicinal plants; Potential risks